1992
DOI: 10.1046/j.1537-2995.1992.32492263446.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of cotton wool filtration of platelet concentrates obtained by automated and manual apheresis

Abstract: The effect of cotton wool filtration of apheresis platelet concentrates (PCs) on platelet viability and complement activation was evaluated by two laboratories. PCs were prepared by automated (Lab A, n = 5) or manual (Lab B, n = 5) apheresis. After storage for 1 day, the PC was filtered through cotton wool before transfusion on one occasion and, on the other occasion, filtered through a standard screen filter before transfusion to the same donor. Five paired studies were performed by each laboratory. Except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
(6 reference statements)
0
16
2
Order By: Relevance
“…Complement has been shown to be activated during storage of PC and it has been postulated that indirect effects of C3a could be responsible for platelet activation [18, 34, 35]. In this study no correlation was observed between increased C3a levels and platelet activation as determined by CD62 expression.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Complement has been shown to be activated during storage of PC and it has been postulated that indirect effects of C3a could be responsible for platelet activation [18, 34, 35]. In this study no correlation was observed between increased C3a levels and platelet activation as determined by CD62 expression.…”
Section: Discussioncontrasting
confidence: 59%
“…The reason why there was no increase in IL–1β levels as found in other studies is not clear [8, 9, 10]. It may be because increased levels of IL–1β have so far been only demonstrated in pooled donor PC [8, 9, 10, 16, 18]. The mean number of WBCs at day 0 per apheresis in this study [0.74×10 9 (0.38–1.08)] or per liter [3.7×10 9 (1.4–5.4)] is not very different from that found in other studies with PC [8, 9, 10, 29], but is higher than that obtained with new plateletpheresis systems (such as the Cobe Spectra LRS and the Fenwal Amicus) [30].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Leaving collected blood at room temperature accelerates com plement activation [2]. The single donor apheresis pro cedure elicited much higher C3a levels in PC products than those of random donor PCs [3]. Holme et al [3] found a small, temporary reduction of leukocyte counts in volunteers after a 30-min infusion of stored autolo gous apheresis PCs.…”
Section: Methodsmentioning
confidence: 99%
“…The single donor apheresis pro cedure elicited much higher C3a levels in PC products than those of random donor PCs [3]. Holme et al [3] found a small, temporary reduction of leukocyte counts in volunteers after a 30-min infusion of stored autolo gous apheresis PCs. Although we do not have much knowledge of these side effects on the transfusion of blood products, including high concentrations of anaphylatoxins, it may well be beneficial to reduce deleterious reac tions following transfusion of PCs with high anaphylatoxin levels.…”
Section: Methodsmentioning
confidence: 99%